132 ANTI-REFLUX SURGERY FOR CONTROLLING RESPIRATORY SYMPTOMS OF GASTRO-ESOPHAGEAL REFLUX DISEASE: A SYSTEMATIC REVIEW AND META-ANALYSIS. (14th September 2020) - Tustumi, F; Bernardo, W; Rocha, J; Szachnowicz, S; Seguro, F; Bianchi, E; Takeda, F; Miranda Neto, A; Sallum, R; Cecconello, I
Abstract:  : Gastro-esophageal reflux disease (GERD) patients have a higher prevalence of airway symptoms, such as chronic cough, wheezing, and hoarseness. The therapeutic management of patients with these symptoms is controversial. Therefore, this study aims to perform a systematic review and meta-analysis evaluating the efficacy of anti-reflux surgery for controlling respiratory symptoms related to GERD. Methods: A systematic review and meta-analysis was performed. Extraction of the data concerning proportions of participants who were not free of respiratory symptoms related to GERD (cough, wheezing, hoarseness) or not substantially improved at follow-ups (failure to cure) was performed. Results: Of the screened articles, 61 were included for meta-analysis, with a cumulative sample size of 3, 869 patients. Of all the included patients, after anti-reflux surgery, the general symptoms improvement was 80% (95% CI 75.2–84%). The numbers needed to harm (NNH) and the numbers needed to treat (NNT) were 15.21 and 1.23, respectively. Of the included patients, 83.4% (95% CI 78.3–87.5%) patients reported improvement in cough symptoms after surgery. For the wheezing symptom, 71.5% (95% CI 62.9–78.8%) reported improvement after surgery. Moreover, surgery presented better results in improving respiratory symptoms than medical therapy (risk difference: -0.46; 95% CI -0.77, −0.16). Conclusion: Physicians should strongly consider surgical anti-reflux procedures for controlling respiratory symptoms in GERD patients after proper patient selection. Anti-reflux surgery has shown high efficacy in improving respiratory symptoms related to GERD, even when compared to medical therapy.